The relationship between performance (tournament progression), daily stress and perceived exertion in male participants of professional squash tournaments - Montanus, Munro (MRC/UCT RU for Exercise and Sport Medicine, 2016)
Squash is a popular sport that is played by over 15 million people in 120 countries. Squash is a sport requiring extreme levels of fitness and skill to be proficient at. Squash being a high impact, fast sport that relies on consistency, strength and skill, players often experience stress. This stress is mainly due to the intensity of the matches, but also due to the short duration of the tournaments, which places a lot of pressure on the participants to do well. Stress in sport has been shown to be a critical component in the performance of an individual athlete as well as in team sports. Stress in sport may be categorised as competitive and organisational as well as acute. Not being able to cope with stress may have varied affects for athletes. These include increased anxiety and aggression; decreased enjoyment and self-esteem; and most importantly a decrease in performance expectations and performance difficulties. Furthermore, if an athlete believes he or she cannot resolve the demands of the competitive environment, negative physical and emotions can affect performance. The ability to compete with the presence of different stressors is thus necessary for an athlete to perform at his or her best. Aim and objectives The specific objectives were to establish whether a) Anthropometric and demographic characteristics, b) Daily Stress as measured by the Daily Analysis of Life Demands for Athletes (DALDA) and c) Rate of Perceived Exertion (RPE) as measured by the Borg Scale were associated with competition performance as measured by winning/losing games in national squash tournaments.